Meta-Analysis of Sex Differences in ADHD Symptoms and Associated Cognitive Deficits. Issue 12 (October 2021) - Loyer Carbonneau, Maryanne; Demers, Martin; Bigras, Marc; Guay, Marie-Claude
Objective: A meta-analysis was carried out to determine whether there are sex differences among children and adolescents with ADHD on the primary symptoms of ADHD and on executive and attentional functioning.Method : Studies published from 1997 to 2017 comparing boys and girls with a valid ADHD diagnosis were retained.Results: The meta-analysis found boys with ADHD to be more hyperactive than girls with ADHD and boys to have more difficulties in terms of motor response inhibition and cognitive flexibility. Results also confirm that youths with ADHD have more executive deficits than non-ADHD peers have, but there is no sex difference in this regard.Conclusion : Results show that there are sex differences in the behavioral expression of the difficulties related to ADHD. This highlights the importance of pursuing research to refine the profile of girls with ADHD and to develop diagnostic criteria adapted to each sex.